Characteristics of vaginal and vulvar microbiota in patients with vulvar precancerous lesions and vulvar squamous cell carcinoma - Dunaevskaya , V. (Journal of Education, Health and Sport, 2024)
The aim of the study was to analyze the composition of the microbiota of the vagina and vulva in patients with precancerous lesions of the vulva in comparison with healthy controls and in women with vulvar cancer. Materials and methods. 286 women with vulvar lesions aged from 25 to 70 years and 60 gynecologically healthy women (30 under 50 years and 30 after 50 years) were included in the study. Patients with vulvar lesions were divided into 5 groups: 87 women with high-grade intraepithelial neoplasia of the vulva (VHSIL) dependent on the human papilloma virus (HPV) (Group 1 - G1), 154 women with differentiated vulvar intraepithelial neoplasia (dVIN) independent of HPV (Group 2 – G2), 9 patients with Paget's disease (Group 3 – G3),, 8 women with melanoma in situ of the vulvar skin (Group 4 – G4), and 28 patients with vulvar squamous cell carcinoma (VSCC) (Group 5 – G5). The results of the study showed that among patients with precancerous lesions of the vulva, the vaginal microbiota of persons with VHSIL is characterized by an increase in facultative and obligate anaerobes, fungi of the genus Candida spp., as well as Ureaplasma spp., Mycoplasma hominis, compared to patients with dVIN. A characteristic feature of the vaginal microbiota of dVIN patients was a high concentration of Prevotella spp.Healthy vulvar skin of patients with precancerous lesions resembled the vaginal and skin microbiome composition of control groups, including genera of Prevotella, Lactobacillus, Gardnerella, Staphylococcus and Corynebacterium. The affected vulvar skin of patients with VHSIL showed an increase in taxa from the genus Prevotella spp., Fusobacteria spp. and Peptostreptococcus spp. Affected vulvar skin of patients with dVIN was characterized by enrichment of taxa from the genus Prevotella sgp., Fusobacteria spp., Atopobium vaginae and depletion of Corynebacterium spp., Lactobacillus spp., Staphylococcus spp., Peptostreptococcus spp. compared to unaffected skin. Conclusions. The study showed a change in the composition of the vaginal microbiota in precancerous diseases and cancer of the vulva. A deeper understanding of the complex interaction between the host and microorganisms in the vaginal area is promising for identifying new strategies in the field of cancer prevention and treatment.